Application of Sainspreneur to Grow Independence and Entrepreneurial Spirit of Elementary School Students - Lestari, Ani Puji; Purwandari, Ristiana Dyah (UM Purwokerto Press, 2024)
This study aims to determine the influence of sciencepreneur learning on learning independence and entrepreneurial spirit of grade IV students at SD Negeri 1 Pakelen for the 2022/2023 academic year. This research uses a quantitative research approach, with associative quantitative research types, and uses quantitative analysis methods (numerical data). Data on learning independence and entrepreneurial spirit were collected using observations using assessment instruments in the form of rubrics. The sample in this study amounted to 22 learners. The research data were processed using a simple linear regression test with the results of the influence of sciencepreneur learning on learning independence t-count = 6.103 and t-table =2.086 means t-count > t-table. For the effect of sciencepreneur learning on entrepreneurial spirit, t count = 7.813 and t table = 2.086 means t-count > t-table. Based on the results of this study, it shows that there is an influence of sciencepreneur learning on learning independence and entrepreneurial spirit of grade IV students of SD Negeri 1 Pakelen for the 2022/2023 academic year.